Elimination of low‐inversion‐efficiency induced artifacts in whole‐brain MP2RAGE using multiple RF‐shim configurations at 7 T. (4th August 2020) - Oran, Omer F.; Klassen, L. Martyn; Gilbert, Kyle M.; Gati, Joseph S.; Menon, Ravi S.
Abstract : The magnetization‐prepared two‐rapid‐gradient‐echo (MP2RAGE) sequence is used for structural T 1 ‐weighted imaging and T 1 mapping of the human brain. In this sequence, adiabatic inversion RF pulses are commonly used, which require the B 1 + magnitude to be above a certain threshold. Achieving this threshold in the whole brain may not be possible at ultra‐high fields because of the short RF wavelength. This results in low‐inversion regions especially in the inferior brain (eg cerebellum and temporal lobes), which is reflected as regions of bright signal in MP2RAGE images. This study aims at eliminating the low‐inversion‐efficiency induced artifacts in MP2RAGE images at 7 T. The proposed technique takes advantage of parallel RF transmission systems by splitting the brain into two overlapping slabs and calculating the complex weights of transmit channels (ie RF shims) on these slabs for excitation and inversion independently. RF shims were calculated using fast methods implemented in the standard workflow. The excitation RF pulse was designed to obtain slabs with flat plateaus and sharp edges. These slabs were joined into a single volume during the online image reconstruction. The two‐slab strategy naturally results in a signal‐to‐noise ratio loss; however, it allowed the use of independent shims to make the B 1 + field exceed the adiabatic threshold in the inferior brain, eliminating regions of low inversion efficiency. Accordingly, the normalized root‐mean‐square errors in the inversion were reduced to below 2%. The two‐slab strategy was found to outperform subject‐specific k T ‐point inversion RF pulses in terms of inversion error. The proposed strategy is a simple yet effective method to eliminate low‐inversion‐efficiency artifacts; consequently, MP2RAGE‐based, artifact‐free T 1 ‐weighted structural images were obtained in the whole brain at 7 T. Abstract : T 1 ‐weighted structural brain images obtained using MP2RAGE suffer from low‐inversion‐efficiency induced artifacts at ultra‐high magnetic fields. This study aims to eliminate these artifacts at 7 T. The proposed "two‐slab strategy" takes advantage of parallel RF transmission systems by splitting the brain into two slabs and calculating the RF shim configurations independently for the slabs. The strategy was found to eliminate low‐inversion regions; consequently, artifact‐free T 1 ‐weighted structural images were obtained in the whole brain.